Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Pelanggan Pabrik Tahu Kelurahan Sisipan Kecamatan Batui: The Effect of Product Quality and Price on Customer Satisfaction Tofu Factory Sisipan Village Batui District - Fitriani Mas'ud; Ichsan Milang (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2020)
The study was conducted to determine and analyze the effect of product quality and price on customer satisfaction at the Tofu Factory in Sisipan Village. Sampling is used by accidental sampling. The sample is 100 respondents, namely the residents of the Sisipan village who buy tofu. The data analysis technique used Multiple Linear Regression Analysis, Correlation Coefficient (r), Coefficient of Determination (R2), F-test, and t-test. The results of the regression analysis Y = 4.727 + 0.324X1 + 0.165X2. Shows that product quality and price simultaneously have a positive and significant effect on customer satisfaction (Y). The results of the correlation coefficient analysis (r) of 0.863 show that there is a very strong relationship between product quality and price on customer satisfaction. The coefficient of determination (R2) of 0.714 or 71.4 means that the magnitude of the influence of product quality and price on customer satisfaction and the remaining 28.6% is determined by variables outside the model being analyzed. Hypothesis testing is obtained that Fcount 13,236 > Ftable 3,09. This shows that H0 is rejected and Ha is accepted. The t-test of Product Quality and Price has a positive and significant effect on customer satisfaction where (2,464, and 1,885) > t table (1,660) and has a probability value of 0,001, and 0,002 < 0,05. It is seen that product quality most dominantly affects customer satisfaction.